A new species of Melanoseris (Lactucinae, Cichorieae, Asteraceae) from SW Xizang, China, based on morphological and molecular data - Yin, Zhi-Jian; Kilian, Norbert; Li, Bing-Zhang; Sun, Hong-Yan; Zhao, Ming-Xu; Wang, Ze-Huan (Phytotaxa, 2018)
Melanoseris jilongensis from SW Xizang, China, is described as a species new to science and illustrated, and its threat status is also assessed. It morphologically resembles M. macrorhiza, but differs in particular in leaf morphology, indumentum and achene characters. Molecular phylogenetic analysis based on nrITS and plastid DNA sequences revealed discordance between both DNA datasets as well as between morphological similarity and phylogenetic position. As in other cases of Sino-Himalayan taxa of the Melanoseris lineage, an event of reticulation in the speciation of M. jilongensis seems to have been taken place.